Development of a method for producing a healthy drink based on fermented beet juice - Stetsenko, Natalia; Goyko, Iryna (My University, 2021)
The object of research is a method of producing a fermented drink from natural raw materials, the consumption of which will provide the human body with probiotics, prebiotics, vitamins and antioxidants. The work used general scientific research methods, in particular, analysis and synthesis, as well as physicochemical methods for determining the composition and properties of raw materials and the finished product. Beetroot and its juice are insufficiently used in the food and processing industries, therefore this particular type of raw material has great reserves and prospects for creating health products. The work is aimed at improving the method of obtaining fermented beet juice enriched with ginger extract. For the production of the drink, the root crops of the Cylindra variety were chosen, which had a high content of dry substances and sugars, and were also characterized by a better storage capacity with minimal losses of biologically active substances. It has been established that when obtaining juice, it is advisable to process crushed pectolytic beets with the enzyme preparation Fructocyme MA-X-Press (manufacturer Russia). This makes it possible to increase the juice yield by 14.9 %, the amount of dry matter by 2.1 % and the sugar content by 1.7 %. To ferment the juice used bacterial preparations of lacto- and bifidobacteria in the amount of 5 % by weight of raw materials. The fermentation was carried out at a temperature of 37 °C for 24 hours. It was found that when using the preparation of B. longum bifidobacteria, which have good stability in an acidic medium, a higher fermentation rate is achieved. To enrich the drink with substances with antioxidant properties, ginger root extract was used. The health-improving effect of the fermented drink is due to the use of exclusively natural plant materials and the use of probiotic cultures of microorganisms in the technological process, which improve the functioning of the gastrointestinal tract and are factors that stimulate the immune system. Об’єктом дослідження є спосіб виробництва ферментованого напою з натуральної сировини, споживання якого дозволить забезпечити організм людини пробіотиками, пребіотиками, вітамінами та антиоксидантами. В роботі використані загальнонаукові методи дослідження, зокрема, аналізу та синтезу, а також фізико-хімічні методи визначення складу та властивостей сировини, та готового продукту. Столовий буряк та його сік не достатньо використовують у харчовій та переробній промисловості, тому саме цей вид сировини має великі резерви та перспективи для створення продукції оздоровчого призначення. Робота направлена на удосконалення способу отримання збродженого бурякового соку, збагаченого екстрактом імбиру. Для виробництва напою обрано коренеплоди сорту Циліндра, які мали найвищий вміст сухих речовин та цукрів, а також характеризувалися найкращою здатністю до зберігання з мінімальними втратами біологічно активних речовин. Встановлено, що при отриманні соку доцільно проводити оброблення подрібнених буряків пектолітичним ферментним препаратом Фруктоцим МА-Х-Прес (виробник Російська Федерація). Це дозволяє підвищити вихід соку на 14,9 %, кількість сухих речовин – на 2,1 % та вміст цукрів – на 1,7 %. Для зброджування соку використовували бактеріальні препарати лакто- та біфідобактерій у кількості 5 % до маси сировини. Сквашування проводили за температури 37 °С протягом 24 год. Встановлено, що при використанні препарату біфідобактерій В. longum, які мають хорошу стійкість у кислому середовищі, досягається більш висока швидкість сквашування. Для збагачення напою речовинами з антиоксидантними властивостями використовували екстракт кореню імбиру. Оздоровча дія ферментованого напою зумовлена використанням виключно натуральної рослинної сировини та застосуванням у технологічному процесі пробіотичних культур мікроорганізмів, які поліпшують роботу шлунково-кишкового тракту та є чинниками стимулювання імунітету.
Keywords: beetroot; beet juice; fermented juice; ginger extract; health drink; столовий буряк; буряковий сік; ферментований сік; екстракт імбиру; оздоровчий напій; кафедра технології оздоровчих продуктів